On taxing wildlife films and exposure to nature - Wunder, Sven; Sheil, D. (Cambridge University Press, 2013)
Some conservation finance strategies feature taxes on nature's benign, and arguably educational, uses. This applies to a recent proposal to extract payment from producers of nature films and also to past efforts to raise entrance fees to protected areas. We argue that, as they are currently formulated, it is misleading to label these proposals as payments for environmental service schemes, as they lack voluntary and conditional payments. Rather, they are a form of taxation. Such revenue-seeking measures may prove to be short-sighted. They will raise prices and curtail the demand for those environmental services that embody some element of education, thus reducing public exposure to nature. This could diminish public awareness, curb people's biophilia and devalue Nature's ‘existence values’. This drive for more conservation cash income in the short term could undermine a broad, long-term societal basis for conservation and its future financing.